2020 IEEE International Conference on Image Processing (ICIP) 2020
DOI: 10.1109/icip40778.2020.9191127
|View full text |Cite
|
Sign up to set email alerts
|

Cycle GAN-Based Data Augmentation For Multi-Organ Detection In CT Images Via Yolo

Abstract: We propose a deep learning solution to the problem of object detection in 3D CT images, i.e. the localization and classification of multiple structures. Supervised learning methods require large annotated datasets that are usually difficult to acquire. We thus develop a Cycle Generative Adversarial Network (CycleGAN) + You Only Look Once (YOLO) combined method for CT data augmentation using MRI source images to train a YOLO detector. This results in a fast and accurate detection with a mean average distance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Then, the way in which the generated and real images are used in different phases needs to be emphasized again. In 2020, Maryam Hammami et al proposed a CycleGAN and YOLO combined model for data augmentation and used generated data and real data to train a YOLO detector, in which generated data and real data are simultaneously input into YOLO for training [61]. In our study, the detector was trained using only generated images in the pre-training phase and only real images in the transfer learning phase, which is a typically network-based deep transfer learning method.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the way in which the generated and real images are used in different phases needs to be emphasized again. In 2020, Maryam Hammami et al proposed a CycleGAN and YOLO combined model for data augmentation and used generated data and real data to train a YOLO detector, in which generated data and real data are simultaneously input into YOLO for training [61]. In our study, the detector was trained using only generated images in the pre-training phase and only real images in the transfer learning phase, which is a typically network-based deep transfer learning method.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional augmentation methods, mostly based on image processing techniques, generative models such as GANs can capture the semantic features of images used for training and generate similar but diferent images to enhance the quantity and diversity of training data. Such capability of GANs has driven its usage in image augmentation for various computer vision tasks, including classifcation [23,24], object detection [25,26], and semantic/image segmentation [27][28][29][30]. Tese prior studies have validated the efectiveness of GANs as an image augmentation technique.…”
Section: Data Augmentation Techniquesmentioning
confidence: 99%
“…The self-attention MADGAN could detect AD at an early stage, with an area under the curve of 0.727, and AD at a late stage with AUC 0.894, whereas it achieved AUC 0.921 for brain metastases detection on T1c scans. Moreover, Maryam Hammami et al [42] designed a combined Cycle GAN and YOLO method for CT data augmentation. The experimental findings showed that detection was speedy and accurate, with an average distance of 7.95 ± 6.2 mm, which was particularly superior to detection without being augmented.…”
Section: Related Workmentioning
confidence: 99%